Electromagnetic navigational bronchoscopy-directed dye marking for locating pulmonary nodules. Issue 1141 (10th February 2020) - Wang, Long-long; He, Bi-fang; Cui, Jing-hua; Gao, Xing-lin; Chen, Ping-ping; Zhong, Wen-zhao; Liao, Ri-qiang; Li, Jing; Sun, Jia-yuan
Abstract: Background: Small peripheral pulmonary nodules, which are usually deep-seated with no visual markers on the pleural surface, are often difficult to locate during surgery. At present, CT-guided percutaneous techniques are used to locate pulmonary nodules, but this method has many limitations. Thus, we aimed to evaluate the accuracy and feasibility of electromagnetic navigational bronchoscopy (ENB) with pleural dye to locate small peripheral pulmonary nodules before video-associated thoracic surgery (VATS). Methods: The ENB localisation procedure was performed under general anaesthesia in an operating room. Once the locatable guide wire, covered with a sheath, reached the ideal location, it was withdrawn and 0.2–1.0 mL of methylene blue/indocyanine green was injected through the guide sheath. Thereafter, 20–60 mL of air was instilled to disperse the dye to the pleura near the nodules. VATS was then performed immediately. Results: Study subjects included 25 patients with 28 nodules. The mean largest diameter of the pulmonary nodules was 11.8 mm (range, 6.0–24.0 mm), and the mean distance from the nearest pleural surface was 13.4 mm (range, 2.5–34.9 mm). After the ENB-guided localisation procedure was completed, the dye was visualised in 23 nodules (82.1%) using VATS. The average duration of the ENB-guided pleural dye marking procedure was 12.6 min (range, 4–30 min). The resection margins were negative in all malignant nodules. Complications unrelated to the ENB-guided localisation procedure occurred in two patients, including one case of haemorrhage and one case of slow intraoperative heart rate. Conclusion: ENB can be used to safely and accurately locate small peripheral pulmonary nodules and guide surgical resection. Trial registration number: ChiCTR1900021963.